Audit Manajemen Inovasi Organisasi Agar Lebih berdaya saing - Wahono Wahono; Mahardika Susanto (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2021)
The goal of this research is to audit and compare the innovation management capabilities of the two organizations using the audit tools proposed by Tidd and Bessant (Managing Innovation: Integrating Technological, Market and Organizational Change, 5th ed. Wiley, West Essex, 2014) which consists of from five dimensions: Strategy, Innovation Process, Learning, Innovative Organization, and Linkages. The sample was selected from each organization from the High Suggestion Department (HSD) and the Low Suggestion Department (LSD). Audit questionnaires were distributed to respondents. The results obtained from this study were processed and analyzed. Comparisons were made between the two organizations in terms of their innovation management capabilities. In addition, comparisons were made between HSD and LSD in each organization. Of the five tested dimensions of Audit has a high score; Therefore, it can be concluded that the organizations in this study have a higher innovation management capability. In addition, every organization must keep the various components of innovation management in balance to maintain them.